2011
DOI: 10.1021/jp112085s
|View full text |Cite
|
Sign up to set email alerts
|

Localized Plasmons in Noble Metal Nanospheroids

Abstract: For the entire range of spheroidal noble metal nanoparticles, including spheres, rods, and disks, the optical properties are investigated as a function of their geometry and size by means of extinction spectra obtained by numerical methods. For spherical silver and gold particles, Mie theory is used to identify multipole plasmon resonances up to hexadecupole order as a function of particle radius. With increasing particle dimensions, higher-order multipole modes become more important. Moreover, the similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 57 publications
5
52
0
Order By: Relevance
“…Similar phenomenon was also reported in Ag and Au NPs . Although numerical simulation can reproduce the blueshift phenomenon, it is unable to reveal the underlying physics. The blueshift effect can be explained by “LC circuit model.” If a nanoparticle is made of plasmonic material and its size is much smaller than the wavelength of incident light, it effectively behaves as a “nanoinductor” due to the negative real part of the permittivity inside the particle .…”
Section: Resultssupporting
confidence: 71%
“…Similar phenomenon was also reported in Ag and Au NPs . Although numerical simulation can reproduce the blueshift phenomenon, it is unable to reveal the underlying physics. The blueshift effect can be explained by “LC circuit model.” If a nanoparticle is made of plasmonic material and its size is much smaller than the wavelength of incident light, it effectively behaves as a “nanoinductor” due to the negative real part of the permittivity inside the particle .…”
Section: Resultssupporting
confidence: 71%
“…For Al nanospheres, the dipole (m = 1) resonance dominants for size 20 nm, the quadrupole (m = 2) resonance mode appears for size !30 nm, and octupole (m = 3) resonance mode for size !80 nm. In comparison, the Au nanosphere exhibits multipolar peaks at much larger size (!140 nm) [21]. Figure 3(b) shows the calculated wavelength shift (Δλ p ) with nanosphere size.…”
mentioning
confidence: 99%
“…Unfortunately, there is no exact analytical formula for the influence of retardation on the quasi-static dipolar resonance wavelength and its dependence on the relevant axis length. However, simulations and experiments revealed that the dependence of the dipolar resonance on axis length shows the characteristics of a second-order polynomial [13,16,40]. This means that the study of a restricted range of axis lengths far from the quasi-static limit results in quasi-linear scaling as experimentally observed.…”
Section: Discussionmentioning
confidence: 88%